Moral identity in relation to emotional well-being: a meta-analysis - Goering, Marlon; Espinoza, Carlos N.; Mercier, Alecia; Eason, Emma K.; Johnson, Charles W.; Richter, Caroline G. (Frontiers in Psychology, 2024)
Introduction This meta-analytic review surveyed previous empirical studies that examined links between moral identity and indicators of emotional well-being. Additionally, this meta-analysis examined cultural origin as a moderator, testing if links between moral identity and emotional well-being differ in collectivistic vs. individualistic countries. Methods A systematic literature review was conducted through ProQuest’s 65 databases and PubMed. A random-effect meta-analysis and subgroup analyses were conducted using Comprehensive Meta-Analysis 4.0 (CMA) software. Results Drawing on 27 eligible studies, moral identity was associated with greater emotional well-being (r = 0.27, p < 0.001). Follow up analyses on individual dimensions showed medium effect sizes in links between moral identity and greater happiness or positive affect (r = 0.28, p < 0.001), greater sense of purpose or meaning in life (r = 0.29, p < 0.001), and higher self-esteem (r = 0.25, p < 0.001). Moreover, moral identity was associated with greater life satisfaction showing a small effect size (r = 0.15, p = 0.011). Results showed that effect sizes of links between moral identity and overall emotional well-being did not significantly differ by cultural origin. However, effect sizes tended to be larger in the nine studies that were conducted in collectivistic countries (r = 0.30, p < 0.001) as compared to the 15 studies that were conducted in individualistic countries (r = 0.27, p < 0.001). Discussion The results of this meta-analysis indicate a robust empirical relationship between moral identity and emotional well-being that is present across various dimensions of emotional well-being and in both individualistic and collectivistic cultures. Systematic review registration https://osf.io/94f8b/?view_only=6db54da0fa304c83993d0438ecb5c637